Guidelines and standards for environmental pollution control in Nigeria - Federal Environmental Protection Agency (FEPA) ({Abuja} : Federal Environmental protection Agency (FEPA), 1991)
The Federal Government of Nigeria through the promulgation of Decree 58 of December 1988, established the Federal Environmental Protection Agency (FEPA). By Section 16 and 17 of the Decree, the Agency is mandated to protect, restore and preserve the ecosystems of the Nigerian environment.
usc 12/11/2021
Ref.
Keywords: Nigeria